Managing intellectual assets in the digital age - Matsuura, Jeffrey H., 1957- (Artech House communications law and policy library., 2003)
Written for technology professionals and business managers/owners alike, this new, easy-to-understand book provides you with a comprehensive overview of the key legal and economic issues that affect rights of access and use for intellectual property and knowledge assets, with special emphasis on computer software, Internet content, and digital media. It is the first book to address management of both traditional intellectual property and the broader set of knowledge assets in a single resource. It presents these subjects in a style appropriate for a wide range of practitioners who are not intellectual property or knowledge management specialists, and approaches the challenge of managing these assets from a multidisciplinary perspective.